2018
DOI: 10.3233/jad-170905
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy and Potentially Inappropriate Medication in People with Dementia: A Nationwide Study

Abstract: Use of polypharmacy and PIM were widespread in the older population and more so in people with dementia. This could have negative implications for patient-safety and demonstrates the need for interventions to improve drug therapy in people with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
68
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 35 publications
7
68
3
3
Order By: Relevance
“…15 The finding of our study is also supported by an Australian study involving 547 participants in residential aged care facilities that showed that people exposed to PIMs (defined by 2015 Beers criteria) were more likely to be older and have a diagnosis of dementia (P = .002). In addition, STOPP-listed PIP involving nonsteroidal anti-inflammatory drugs (NSAIDs) were more frequent in people not dispensed medicines for dementia than people dispensed medicines for dementia, including long-term use of NSAIDs (11.3% vs 7.2%, P < .0001) ( green list) higher than that of participants without dementia.…”
Section: Prevalence Of Individual Stopp Criteriasupporting
confidence: 81%
See 2 more Smart Citations
“…15 The finding of our study is also supported by an Australian study involving 547 participants in residential aged care facilities that showed that people exposed to PIMs (defined by 2015 Beers criteria) were more likely to be older and have a diagnosis of dementia (P = .002). In addition, STOPP-listed PIP involving nonsteroidal anti-inflammatory drugs (NSAIDs) were more frequent in people not dispensed medicines for dementia than people dispensed medicines for dementia, including long-term use of NSAIDs (11.3% vs 7.2%, P < .0001) ( green list) higher than that of participants without dementia.…”
Section: Prevalence Of Individual Stopp Criteriasupporting
confidence: 81%
“…In addition, STOPP-listed PIP involving nonsteroidal anti-inflammatory drugs (NSAIDs) were more frequent in people not dispensed medicines for dementia than people dispensed medicines for dementia, including long-term use of NSAIDs (11.3% vs 7.2%, P < .0001) ( green list) higher than that of participants without dementia. 15 The finding of our study is also supported by an Australian study involving 547 participants in residential aged care facilities that showed that people exposed to PIMs (defined by 2015 Beers criteria) were more likely to be older and have a diagnosis of dementia (P = .002). 25 In contrast, a systematic review looking at PIP in people with dementia found that dementia was associated with a decrease in the likelihood of PIMs.…”
Section: Prevalence Of Individual Stopp Criteriasupporting
confidence: 81%
See 1 more Smart Citation
“…Old age is associated with a decrease of oxidative metabolism, causing an extension on drug half-life due to changes in pharmacokinetics and pharmacodynamics (Taipale et al, 2015;Hessmann et al, 2018). In fact, the prolonged use of these drugs (over 2 months) in advanced age has shown to produce serious side effects, causing tolerance and dependence, increased risk of falls and fractures as well as an impairment of cognitive processes (Pharmd et al, 2003;Obradovi et al, 2005;Stewart, 2005;Rissman et al, 2007;Savić et al, 2010;Rosenberg et al, 2012;Makaron et al, 2013;Biétry et al, 2017;Nørgaard et al, 2017;Duke et al, 2018;Picton and Pharm, 2018;Underlien et al, 2018;Scott and Aricescu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Inequality in access to physicians means that not all patients with dementia are offered systematic medical follow-up, and therefore treatable conditions may be overlooked or mismanaged, leading to accelerated functional decline, hospitalizations and increased mortality, and thus increased healthcare costs. Polypharmacy with adverse interactions and an unfavorable risk-benefit ratio is another frequent occurrence in this population, which requires systematic medical follow-up [3,4]. Moreover, for patients with dementia, treatment practices for associated medical conditions may vary due to uncertainty with regard to the balance between benefits and adverse effects, and due to a lack of scientific certainty.…”
Section: Introductionmentioning
confidence: 99%